2010
DOI: 10.2353/ajpath.2010.090779
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Fanconi Anemia FANCD2 Protein in Sporadic and Metastatic Human Breast Cancer

Abstract: FANCD2, a pivotal protein in the Fanconi anemia and BRCA pathway/network, is monoubiquitylated in the nucleus in response to DNA damage. This study examines the subcellular location and relationship with prognostic factors and patient survival of FANCD2 in breast cancer. Antibodies to FANCD2 were used to immunocytochemically stain 16 benign and 20 malignant breast specimens as well as 314 primary breast carcinomas to assess its association with subcellular compartment and prognostic factors using Fisher's Exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 59 publications
2
36
0
Order By: Relevance
“…Interestingly, a very recent immunohistochemical study showed that a significant proportion of malignant breast tumors had lost expression of nuclear FANCD2 but retained cytoplasmic expression, whereas benign lesions retained both nuclear and cytoplasmic staining (32). These observations are consistent with FANCD2 nuclear import serving as a tumor-suppressing mechanism.…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, a very recent immunohistochemical study showed that a significant proportion of malignant breast tumors had lost expression of nuclear FANCD2 but retained cytoplasmic expression, whereas benign lesions retained both nuclear and cytoplasmic staining (32). These observations are consistent with FANCD2 nuclear import serving as a tumor-suppressing mechanism.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, analyses of the proliferation marker Ki67 in GBM tissue micro-arrays agree with this hypothesis (Figures 1C and S1C). It is interesting to note that in contrast to these findings, a previous study showed that a cohort of breast tumours exhibiting reduced cytoplasmic FANCD2 expression were correlated with poor survival outcomes [26]. However, our findings are also consistent with previous reports showing that highly proliferative tissues such as testis, tonsils and spleen exhibit high expression of FANCD2 and FANCA, yet non-proliferative tissues such as lung, liver, muscle and the brain exhibit minimal expression of these proteins [9, 10].…”
Section: Discussionmentioning
confidence: 94%
“…In a recent study, FANCD2 was found to be largely cytoplasmic in more malignant human breast tumor tissues. 47 Cytoplasmic localization of FANCD2 in cells, similar to that of FANCI, also probably prevents FA pathway activation, leading to genome instability. It is still unclear what is the precise mechanism that causes the FANCD2 protein mislocalization in these human breast cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear what is the precise mechanism that causes the FANCD2 protein mislocalization in these human breast cancer tissues. 47 It will be interesting to determine whether FANCI may also be abnormally expressed and cytoplasmically localized in human breast cancers and whether this is the result of sporadic mutations that target the C-terminal NLS function of FANCI. It is known that defects in protein NLSs have been associated with human disease conditions, such as numerous cancers and developmental disorders.…”
Section: Discussionmentioning
confidence: 99%